Treatment of oil palm veneer with low molecular weight phenol formaldehyde for high grade laminated veneer lumber - Masseat, Khairul (2017)
The depletion of our tropical timber has encouraged the Malaysian wood based industry to seek alternative raw materials such as fast growing plantation tree also lignocellulosic materials for board production. Oil palm tree (Elaeis guinensis) from agricultural residues is one of the potential alternative raw material in year future especially to be used as components in furniture making. Researches on laminated veneer lumber (LVL) manufactured from oil palm veneers are being developed in line to reduce waste from oil palm biomass. However, there are no information available concerning the effects of oil palm veneer treatment at wet or high moisture content, treated oil palm LVL boards and using high moisture content before hot press to form LVL on physical and mechanical properties. As we know, the properties of oil palm lumber or veneer is less and not as good as wood. Modification and treatment to the raw material from oil palm are needed to enhance the quality and make it stable as normal wood. Therefore, the main objective of this study is to determine the physical and mechanical properties of LVL made from oil palm veneer (OPV) treated with low molecular weight phenol formaldehyde (LMWPF) resin with different resin solid content (30 and 45%) with different initial moisture content (100, 70, 30 and 15%) of veneer before treatment. OPVs were soaked into LMWPF solution and re-dried to 10% MC before being hot pressed. After the optimum or the best initial moisture content before treatment and resin solid content being gathered, other samples by using optimum parameters with moisture content before hot press was targeted at 15% to compare which parameter produced better physical and mechanical properties of oil palm LVL. There was no any additional resin was added to bond the veneers to form the LVL boards. From the study, by using 45% solid content of LMWPF at 15% initial OPV MC before treatment and re-dried to 10% MC before hot press, it’s showed better performance in terms of physical and mechanical properties of oil palm LVL compared to other parameters. The density results were in the same range between treated LVL and untreated LVL which in the range of 446.72 to 653.32 kg/m3 and 591.77 kg/m3 respectively. However, there were significantly different to others physical and mechanical properties test with treated and untreated oil palm LVL. As for thickness swelling (TS) and water absorption (WA), treated LVL showed 0.76 and 24.40% respectively as compared to 2.99 and 63.03% for untreated LVL. While for treated LVL on MOR and MOE parallel to the grain, it produced 38.97 and 4843.5 MPa respectively compared to untreated LVL which only 15.43 and 570.27 MPa respectively. From the result gained, it can be concluded that OPV need to do treatment before product making to enhance quality and comparable to normal wood also can be suggested as a good raw material as a supplement for furniture components in the future.